The Effect of Bargaining Structure on Negotiated Wage Settlements - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1981)
The purpose of this paper is to explore the effect of the structure of collective bargaining on union bargaining power. More specifically, its objective is to determine whether bargaining through employer's association, multi-employer, single (multi-plant) employer or single-plant negotiation units has had an effect on negotiated wage settlements (union wage changes) in the private sector in Canada.